KOMUNKASI ISlAM QURBAN DAN PENSVARlATANNYA - Muhtadin, Muhtadin (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2008)
Generally speaking,  communcation  can be  defined   as an effort   to  intluence.  invite  and tranfer thought, ideology,  knowledge   and acts to others so that  they  want to observe  our thought,   ideology,  knowledge   or acts.  Meanwhile,  communication   of Islam is to invite  or to  tranfer   or  to  impeiemnt   Islamic  ideas,  or  to  persuade   others   to  give   up   what  is forbidden  by god  and to what is commanded by him.A.Hasyami   says that  communication    in Islam is a call for believing   in and  impiementinq Islamic Sharia.  Sim!larly,   Prof   Tone  Yahya Umar,   MA maintains   that  communication    of Islam   a   religious   call   through    persuasion     education,    or   teechinq.     Thus,    Islamic communication as a religious call has a broad and  complex  meaning.In Islam,  sacrifice is slaughtenng  sacrificial animals  (camel,  cow and sheep)  in 10,   11, 12, or 13  of Dzulh!Jjah  intended   to get  closer to  God   Islam commands its followers to  do  the sacrifice as one of religious rites. However,  based  on Ouren and  hadits, Mus/tin scholars have two  different  opinions  on  the status  of sacrifice in Islam :1.     Wajib,  for those able  to sacrifice2.     Sunat muakkad,  for able to sacrificeMeanwhile,   for those  who has passed  aways,  Muslim scholars state  state  that the  sacrifice is allowed  with the following  conditions:1.     it involves those stilt alive2.     the sacrifice is carried out forparticular  will of the death3.       the sacrifice for the death  is categorized  as sadaqa (religious alms)Neverheless,  this kind of sacrifice (for the death)  has never been  practiced  by the  Prophet Muhammad,   Peace be upon  him.